RECONSTRUCTION OF PORNOGRAPHY CRIMINAL REGULATIONS BASED ON PANCASILA JUSTICE VALUES - Mashdurohatun, Anis; Simanjuntak, Alden Juniedy; Zamrudi, Ehwan; Kusuma, Andi; Rabiie, Ahmed (Jurnal Pembaharuan Hukum, 2024)
Pornography in positive law in Indonesia has differences with the views of some indigenous people in Indonesia. The purpose of this study is to find and examine the regulation of pornography crimes that have not been accounted for and to formulate a reconstruction of the regulation of pornography crimes based on Pancasila justice. This legal research is a socio-legal legal research. The results of this study are that the legal regulation of pornography reflected in the current positive legal construction does not fully reflect justice based on Pancasila values, because it ignores cultural rights and human rights. Regulations that are open to multiple interpretations in defining pornography have created a gap for the criminalization of the right to express art and culture. The author recommends that the reconstruction of Article 4 paragraph (1) be directed at stricter normative restrictions by adding the element intentionally and with the intention of arousing sexual desire.